ProGrid: a proxy-based architecture for grid operation and management - Costa, P. V. C.; Zorzo, S. D.; Guardia, H. C. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2003: Anais do XV Symposium on Computer Architecture and High Performance Computing, 2003)
We introduce the ProGrid system, an architecture for computational grids, whose communication and resource management infrastructure is used transparently by the applications. Unlike other grid approaches, either application-centric or system-centric, the model relies on the use of proxy servers to perform additional communications and authentication procedures on behalf of client applications. The purpose of this mechanism is to enable parallel applications to be executed in geographically distributed environments interlinked by an open communication network, such as the Internet, meeting the security requisites desirable for computational grids. Among the common services of a grid, we focus on safe communication and the controlled sharing of available resources. To identify the resources, standards under development are considered for the specification of objects in grids. We also discuss an extension of the functionality of proxy servers to include support for the standardized management of the grid and of the available objects.